Analisis Sistem Kearsipan Surat Masuk Dalam Pengelolaan Proposal Permohonan Bantuan Dana Masjid Di Kota Medan: Studi Kasus Biro Umum Kantor Gubernur Sumatera Utara - Nabila Oktarina Sinulingga; Azhari Akmal Tarigan (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Mail management is an important thing to pay attention to in order to maintain the integrity of the information to be received. In the correspondence system at the North Sumatra Governor's Office, every incoming letter will be received first by the General Bureau to be recorded as an incoming letter archive and then forwarded to the relevant bureau to manage the letter. This paper aims to review the incoming mail management process at the General Bureau and then assess the current system. By using descriptive qualitative methods, the data contained in this paper were obtained through direct observation, interviews and literature studies. So it was found that the incoming mail management system at the General Bureau is currently at a good and efficient stage which is also supported by technological assistance in loading information from each incoming letter.